2004
DOI: 10.1016/j.femsle.2004.03.043
|View full text |Cite
|
Sign up to set email alerts
|

An ffh mutant of Streptococcus mutans is viable and able to physiologically adapt to low pH in continuous culture

Abstract: Previously, we described in Streptococcus mutans strain NG8 a 5-gene operon (sat) that includes ffh, the bacterial homologue of the eukaryotic signal recognition particle (SRP) protein, SR54. A mutation in ffh resulted in acid sensitivity but not loss of viability. In the present study, chemostat-grown cells of the ffh mutant were shown to possess only 26% and 39% of the parental membrane F-ATPase activity and 55% and 75% of parental glucose-phosphotransferase (PTS) activity when pH-7 and pH-5-grown cells, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 35 publications
4
26
0
Order By: Relevance
“…As expected, the enzymatic activity of membrane fractions from acid-shocked (pH 5.0) wild-type cells was significantly increased relative to the pH 7.0-maintained culture and reflects the ability of S. mutans to rapidly adapt to this environmental challenge; this was not the case for the mutant strains in which the specific activities remained unchanged or decreased significantly in response to acid-shock. Expression of the enzymatically active F 1 component was not likely affected by the ffh mutation because we showed that ATPase activity from whole decryptified cells was identical in chemostat-grown wild-type and ffh-mutant MK4 cultures (39). However, differences in activities of membrane fractions were similar to those shown here.…”
Section: H ؉ ͞Atpase Activity In Wild-type and Mutant Strains With Ansupporting
confidence: 79%
See 2 more Smart Citations
“…As expected, the enzymatic activity of membrane fractions from acid-shocked (pH 5.0) wild-type cells was significantly increased relative to the pH 7.0-maintained culture and reflects the ability of S. mutans to rapidly adapt to this environmental challenge; this was not the case for the mutant strains in which the specific activities remained unchanged or decreased significantly in response to acid-shock. Expression of the enzymatically active F 1 component was not likely affected by the ffh mutation because we showed that ATPase activity from whole decryptified cells was identical in chemostat-grown wild-type and ffh-mutant MK4 cultures (39). However, differences in activities of membrane fractions were similar to those shown here.…”
Section: H ؉ ͞Atpase Activity In Wild-type and Mutant Strains With Ansupporting
confidence: 79%
“…Taken together, the results indicate that complete removal of Ffh from S. mutans is not lethal, but does render the organism less able to contend with several environmental stressors. Interestingly, mutant MK4 was shown previously to adapt to acid stress and grow when pH was allowed to drop gradually from normal metabolism, indicating that given time compensatory mechanisms are engaged upon environmental challenge in the absence of an intact SRP pathway (39).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The mechanisms of insertion of the F 1 F 0 ATPase in S. mutans membranes are not known; however, mutations of ffh or yidC2 decrease acid tolerance and membraneassociated ATPase activity (Crowley et al, 2004;Hasona et al, 2005). In previous work, a deletion of yidC1 had no apparent effect on acid tolerance or membrane-associated ATPase activity (Hasona et al, 2005), leading to the hypothesis that, in S. mutans, YidC2 and the SRP pathways are involved in the assembly of the F-ATPase, while YidC1 is not.…”
Section: The C Terminus Of Yidc2 Is Important For Stress Tolerancementioning
confidence: 99%
“…Surprisingly, interruption of ffh was not lethal, in contrast to reports for Escherichia coli (41) and Bacillus subtilis (19), but did render S. mutans sensitive to acid shock (pH 5.0). Mutants subsequently engineered to lack ffh, scRNA, or ftsY, singly or in combination, remained viable in complex growth media under nonstress conditions but were unable to survive at pH 5.0 or with 3.5% NaCl, and growth in the presence of 0.3 mM H 2 O 2 was impaired (10,17). Acid tolerance in S. mutans is mediated in large part by an F 1 F 0 ATPase proton pump (4), and all SRP pathway mutants have decreased membrane-associated ATPase activity, which partially explains their acid sensitivity (10,17).…”
mentioning
confidence: 99%